2013
DOI: 10.1007/978-94-007-6627-3_47
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence in Pulmonary Vasculitis

Abstract: Pulmonary vasculitis is a potentially lethal autoimmune disease characterized by granulomatous inflammation of respiratory tract, necrotizing vasculitis affecting small-to medium-size vessels and antineutrophil cytoplasmic antibodies elevation. Typical therapy involves high-dose glucocorticosteroids combined with cyclophosphamide in a dose 1-2 mg/kg/per day. A high relapse rate in pulmonary vasculitis means prolonged courses of cyclophosphamide in some patients. Carcinogenic effects of cyclophosphamide, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 12 publications
3
14
1
Order By: Relevance
“…For example, in the Westman et al’s study[ 8 ], no case of skin cancer was observed during the first year of follow-up, however, the risk for NMSC was significantly associated with azathioprine therapy for more than 12 mouths (16-fold increase) and with glucocorticoids for more than 48 mouths (20-fold increase). Alternatively, subsequent studies in AASV were consistent with observations in the Westman et al’s study[ 10 , 12 ]. Furthermore, one study found that azathioprine might hasten the induction of NMSC by sensitising the skin cell genome to ultraviolet A radiation[ 24 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…For example, in the Westman et al’s study[ 8 ], no case of skin cancer was observed during the first year of follow-up, however, the risk for NMSC was significantly associated with azathioprine therapy for more than 12 mouths (16-fold increase) and with glucocorticoids for more than 48 mouths (20-fold increase). Alternatively, subsequent studies in AASV were consistent with observations in the Westman et al’s study[ 10 , 12 ]. Furthermore, one study found that azathioprine might hasten the induction of NMSC by sensitising the skin cell genome to ultraviolet A radiation[ 24 ].…”
Section: Discussionsupporting
confidence: 86%
“…As shown in Fig 1 , our initial search rendered 2,762 potentially relevant articles, from which six cohort studies were included[ 8 – 12 , 14 ]. Three studies were monocentric cohorts[ 8 , 12 , 14 ], two study nationwide registry linkage[ 9 , 10 ], and one was a multinational study[ 11 ]. Among these studies, two were carried out in Sweden, one in Germany, one in Poland, one in Denmark and one in Europe and Mexico.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lung cancer is globally responsible for 1.4 million deaths annually and is the leading cause of cancer-related deaths in both women and men [1]. Approximately 80 % of the lung cancer patients have non-small cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 99%